Stern (Todes), Charlotte (audio interview #7 of 7) - Stern (Todes), Charlotte (5/5/1897 - 11/15/1996); Baxandall, Rosalyn, interviewer
INTERVIEW DESCRIPTION - This is the seventh and final interview with Charlotte Todes Stern, conducted in her Columbia University apartment by Ros Baxandall for the Feminist History Research Project. There is a problem with the audio towards the end of the first tape side. Following this interview, the narrator and interviewer stayed in contact and the relationship was important to both. 6/13/1977